Diversity and Distribution of Macroalgae in Beralas Bakau Island, Gunung Kijang District, Bintan Regency - Fadhil Dwi Prakoso; Febrianti Lestari; Tri Apriadi (Jurnal Perikanan dan Kelautan, 2019)
Bintan Regency have potential aquatic resources which have ecologically important value, one of these resources is macroalgae or seaweed. The objective of this study was to determine the composition of species, density, distribution patterns and environmental factors that influence the presence of macroalgae in the waters of the Beralas Bakau island. This research was conducted with a random method of 30 points using a 2x2 m plot. The results of the study found 7 types of macroalgae namely, Acanthophora spicifera, Caulerpa lentillifera, Gracilaria Salicornia, Halimeda opuntia, Kappaphycus cottonii, Padina australis, and Sargassum cristaefolium. The highest density was Sargassum cristaefolium (34.75 ind/m²) and the lowest was H. opuntia (0.25 ind/m²) with a total overall value of species density 51.25 ind/m². The distribution pattern value was uniform with a value of -2.843. Based on the results obtained from the Principal Component Analysis (PCA), the relationship between phosphate parameters and pH was more closely related to the density of macroalgae types compared with other chemical physics parameters